Industrial seating and spinal loading - Eklund, Jörgen (1986)
Little information is available in the literature concerning an ergonomic systems view of industrial seats. This study has been aimed at expanding knowledge of industrial seat design. For this purpose, a model for evaluating industrial seats has been proposed, listing demands and restrictions from the task and the workplace. It also includes responses and effects on the sitter, and methods of measurement for evaluating industrial work seats.